2003
DOI: 10.1074/jbc.m302433200
|View full text |Cite
|
Sign up to set email alerts
|

Ras Signaling and Transcriptional Synergy at a Flexible Ets-1/Pit-1 Composite DNA Element Is Defined by the Assembly of Selective Activation Domains

Abstract: Pit-1 and Ets-1 binding to a composite element synergistically activates and targets Ras-mitogen-activated protein kinase signaling to the rat prolactin promoter. These transcriptional responses appear to depend on three molecular features: organization of the Ets-1/Pit-1 composite element, physical interaction of these two factors via the Pit-1 homeodomain (amino acids 199 -291) and the Ets-1 regulatory III domain (amino acids 190 -257), and assembly of their transcriptional activation domains (TADs). Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…No effect on the synergistic activity of these proteins at the rat prolactin promoter was observed when Ets-1 proteins carrying mutations on their Pit-1 interaction surface, which significantly reduced binding of the two factors in vitro, were used in in situ assays (6). Ets-1 and Pit-1, however, both require specific DNA binding sites at the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…No effect on the synergistic activity of these proteins at the rat prolactin promoter was observed when Ets-1 proteins carrying mutations on their Pit-1 interaction surface, which significantly reduced binding of the two factors in vitro, were used in in situ assays (6). Ets-1 and Pit-1, however, both require specific DNA binding sites at the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The cooperation between PIT1 and ETS family transcription factor in the PRL promoter is also determined by the spacing between these two transcription factors (Duval et al 2003). To examine the effect of the spacing between PIT1-US and GATA-REs on the transactivation of the Tshb gene, we generated TSHb-2G-CAT and THb-4G-CAT, which have an additional 2 or 4 bp insertion of guanines between PIT1-US and GATA-REs respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the synergy of PIT1 with ETS family transcription factor including ETS1 is known to be necessary for the full activation of the Prl gene (Gutierrez-Hartmann et al 2007). Finally, Duval et al (2003) reported that this synergy does not require the physical interaction of PIT1 with ETS1 on DNA but is influenced by the spacing between the binding sites for these transcription factors (8 bp in the wild-type promoter). It should be noted, however, that the cooperation of PIT1 with GATA2 is not conventional synergism but rather derepression against SRBP on SR (Figs 6, 7 and 8).…”
mentioning
confidence: 99%
“…The -domain insertionpoint lies at the boundary between the two TAD exons, R1 and R2, which regulate Pit-1-ETS-1 synergy and Ras response respectively (Duval et al 2003). The lack of requirement for physical interaction between Ets-1 and Pit-1 for either Ras responsiveness or Pit-1-ETS-1 synergy suggests that the -domain may interfere with coactivator recruitment by the Pit-1 and Ets-1 complex.…”
Section: Discussionmentioning
confidence: 99%